Epidemiological Survey of Toxoplasmosis among Aborted Women in Garmian district, Kurdistan Region, Iraq - Ibrahim Ali, Salar (Kurdistan Journal of Applied Research, 2018)
Toxoplasmosis is a zoonotic infection that caused by an obligated intracellular parasite Toxoplasma gondii of many types of tissues, including nervous, muscular and intestinal epithelial tissue. Congenital toxoplasmosis is most severe condition when occurs in early period of pregnancy. The main aim of this study is to determine prevalence of toxoplasmosis among aborted women in Garmian region by using both Latex Agglutination Test (LAT) and Enzyme Linked Immunosorbent Assay (ELISA). The study was carried out in Kalar General Hospital to detect Toxoplasma antibodies among 350 samples, in which 250 samples were from aborted women and 100 samples were from normal birth women as a control. Participants’ age was range from < 18 to > 35 years old. The data were collected form 15th January 2009 to 25th June 2010 by using a special questionnaire form to obtain full information from each participant. For statistical analysis of the data, Statistical Package for Social Sciences (SPSS) version 22 was used. The study showed that (112) cases out of 250 were seropositive for Toxoplasma gondii by using LAT, (65) cases for IgG and (50) cases for IgM by using ELISA. In the abortion group, it showed (87) cases out of 150 were seropositive by using LAT, (51) cases for IgG and (40) cases for IgM (26.6%), whereas in normal birth group (control), it showed (25) case out of 100 were seropositive by using LAT, (14) case for IgG and (10) case for IgM by using ELISA. A High seropositivity percentage was recorded among housewives (35.2%) than teachers and employees (29.4%), (28.5%) respectively. Furthermore, a higher percentage of Toxoplasma seropositivity was recorded in rural area than urban area. The aborted women who were in contact with soil showed the higher rate of Toxoplasma seropositivity (38.7%) than those were not in contact with soil (25%). This study concluded that the prevalence of toxoplasmosis was higher in Garmian region and especially among those women who have lower education level and who live in rural areas.